Data Routing and Spectrum Utilization Techniques in Cognitive IOT Network (International Journal of Innovative Research in Computer Science & Technology, 2021)
Wireless devices increase the comfort of  human life by reducing labor work and data reading  accuracy. Wireless device transfer data though allotted  spectrum or free available spectrum. An IOT device has  limited resources to establish communication between source and destination. So paper has work on cognitive IOT  network which depends on algorithms that can sense  spectrum efficiently and route data. Paper has summarized  various researcher work done for blank spectrum sensing in  cognitive IOT network which may be co-operative or non co-operative in nature. Further some of network routing  issues were explained that were directly or indirectly  depends on hardware limitation, algorithm computation,  etc. Routing algorithms were also list in the work which  was used by scholars to resolve different network issues
Keywords: Cognitive radio; Data Routing; Resource Utilization; Spectrum Sensing